Breastfeeding, Co-Sleeping and Dental Health Advice. Issue 3 (May 2015) - Wert, Katie M. Lapps; Lindemeyer, Rochelle; Spatz, Diane L.
Abstract Purpose: To identify dental health advice offered by healthcare providers (HCPs) to mothers that cosleep and breastfeed at night. Study Design and Methods: Mothers were recruited via local contacts, e-mail, and support groups. In-person, digitally recorded interviews were conducted with 14 cosleeping, breastfeeding mothers with children from 6 months to 2 years. Interviews included seven open-ended questions about cosleeping patterns, night breastfeeding patterns, and dental health advice offered by HCPs. These HCPs included pediatricians, family medicine physicians, midwives, and obstetricians. Interviews were transcribed verbatim and qualitative descriptive analysis was done. Results: The majority of women reported keeping their child in bed with them for most, if not all, of the night. All of the mothers reported breastfeeding on demand. Approximately half of the mothers did not disclose their sleeping patterns to their HCP. Mothers reported few HCPs initiated a discussion on cosleeping or oral hygiene for their child. Clinical Implications: Mothers did not readily share their cosleeping, nor did most HCPs initiate a conversation about cosleeping and dental hygiene. This qualitative study identifies the need for education on anticipatory guidance of oral hygiene discussions from HCPs. As HCPs, it is our responsibility to initiate the conversation with the mother because this study demonstrates that mothers will be unlikely to do so.